Survey of The Physical Condition Level of Male and Female Karate Athletes - Agustin, Richa (International Martial Arts and Culture Journal, 2024)
Studi Purpose This research aims to determine the level of physical condition of male karate athletes in the Pemulutan dojo. Method This type of research is descriptive research with a population of 10 Pemulutan karate dojo athletes. The sampling technique used was a total sampling technique. So the sample in this study amounted to 10 people. The test instrument carried out in this study was a test of the level of physical condition, namely, abdominal muscle endurance, arm and shoulder muscle endurance, general endurance, damn. Results of the data analysis of this research obtained the level of physical condition of men's karate athletes at the Pemulutan dojo in the sufficient category of 9 people. with a percentage of 90% and 1 person with a percentage of 10% has a category after statistical processing, the physical condition of the men's karate athletes at the Pemulutan dojo with an average value of 4.4 lies in the interval 4.0 – 5.9 with a percentage of 90% based on research results carried out, it can be concluded that the level of physical condition of athletes in the Pemulutan dojo in the adequate category lies in the interval 4.0 – 5.9 with a percentage of 90%.